(untitled) (Bangladesh Journal of Zoology, 2024)
The widespread use of the mitochondrial gene, Cytochrome c oxidase subunit I (COI), for molecular identification of moth species is both reliable and time-efficient. In the present study, a total of 26 moths from various regions of Bangladesh were collected, and their COI gene was sequenced. Subsequently, homology searches of these species at NCBI’s GenBank revealed significant similarity across diverse countries of origin except for, Fodina oriolus and Micronia aculeata. We then submitted all COI gene sequences to Genbank, with the exception of two sequences, F. oriolus and M. aculeata, which marked the first submission in the Genbank database. We then used BioEdit and MEGA10 to identify a 582 bp COI gene fragment, which included 353 conserved sites, 229 variable sites, and 180 parsimony-informative sites. In the analysis, the average nucleotide composition showed 29.04% A, 41.06% T, 14.43% G, and 15.46% C, respectively. The value of A+T (70.10%) was greater than G+C (29.90%). On the other hand, the Kimura 2-Parameter algorithm calculated the genetic distances between the 26 moth species, revealing variations ranging from 0.051 to 0.197%. This result showed evidence of interspecies hybridization due to the low levels of interspecies divergence (0.051 to 0.197%). However, the DNA barcode dataset serves as a foundation for identifying moth species and establishing a comprehensive barcode reference library for moth pests in Bangladesh and neighbouring countries. Additionally, it supports integrated pest control efforts and contributes to larger ecological studies. Bangladesh J. Zool. 52(1): 67-79, 2024